Chronobiological features in episodic and chronic migraine - Peres, Mario Fernando Prieto; Gonçalves, Andre Leite; Masruha, Marcelo Rodrigues; Stiles, Marlind Alan; Siow, Charles; Silberstein, Stephen D; Cipolla-Neto, José (Headache Medicine, 2010)
Altered melatonin secretion and circadian, seasonal variations have been shown in migraine patients, but little is known about migraine chronobiological features. Two hundred migraine patients were studied. Headaches were reported to occur after changes in patients sleep schedule (46%), shift work (86%) and traveling across time zones (79%). Patients significantly delayed their sleep phase, 54% shifted their sleep phase. Chronobiology is a relevant aspect in migraine patients.